The Approach Of The Sports Press To Public Relations Activities in Turkey - Aydemir Okay (Selçuk İletişim)
Journalism and public relations are professional fields very close to each other. Despite some evidences regarding the usefulness of public relations supports on news work, a number of studies have described the perceptions of public relations practitioners and journalists as sometimes adversarial,  cooperative, or a love-hate relationship, and mostly skeptical toward each other. Most studies confirm that practitioners try to influence the news process and journalists try to defend against undue influence by sources, too.Although sport is used as a communications vehicle it hasn't been given adequate treatment within public relations literature. The purpose of this study is to indicate how sports writers (referred to as “journalists” in this study) encounter public relations activities of various institutions whilst preparing the sports news, and how they are affected by these activities.